Three hundred verses : musings on life, love and renunciation - Haksar, A. N. D.; Haksar, A. N. D. (tr.) (Gurgaon Penguin RH, 2017)
Young, doe-eyed maidens beguile lovelorn men. Timeless wisdom is dispensed through brief, colourful vignettes. The bounty of the earth is celebrated even as the seasons bear witness to the amorous play of lovers. In Three Hundred Verses, Bhartrihari, one of the greatest Sanskrit poets of all time, brilliantly expounds on our most enduring concerns and dilemmas: living, loving and leaving. Although composed centuries ago, the full force of his genius is abundantly evident in these poems, bursting with lush imagery and brimming with deep philosophical musings. Covering a wide range of themes-from the first stirrings of young love to the challenges of accepting life's transience-these verses are sure to resonate with contemporary readers. By turns playful and wise, A.N.D. Haksar's gorgeous and accessible translation captures the verve, acuity and erotic charge of Bhartrihari's most significant work.
Keywords: Poetry; IFS as an translator; Indian Forign Service